Open to All: Dementia, Creativity, and Open Ecosystem Innovation - Senior, Timothy J. (Frontiers in Sociology, 2019)
In the health arena, open innovation approaches strive to address real-world complexity through driving multi-stakeholder collaborative activities that can better identify and respond to complex health needs. This paper will argue for the value of an open ecosystem innovation approach, one that explores the full implications of what it means to be ‘open’ in a health innovation context. To these ends, the paper will outline the origins of open innovation in the health arena, suggesting that it has become an important site for pushing the limits of open methods and challenging mainstream conceptions of the targets of health innovation. Five guiding principles for open ecosystem innovation will then be proposed, drawing on learning from the Knowledge Exchange Hubs for the Creative Economy funded by the UK’s Arts and Humanities Research Council. These principles point to a configuration of open activities that are maximally sensitive to 1) knowledge diversity in innovation work; 2) the consequences of adopting an open-orientation across all stages of innovation programming; 3) the value of deepening and broadening the targets of innovation activity; 4) the role of mediation in supporting cross-sector partnerships; and, 5) the importance of operating in an adaptive and sustainable manner in the long-term. A follow-on project from the AHRC Hubs – Dementia Connect – sought to apply this learning to an important health focus: dementia and the role played by creative participation in delivering important health outcomes. Through Dementia Connect, the applicability of open ecosystem innovation thinking was assessed, revealing the conditions under which it might deliver innovation-led improvements to the quality of life for those living with a dementia diagnosis. A detailed blueprint for conducting open ecosystem innovation is then proposed in full – a new and comprehensive response to the complex reality of living with a dementia diagnosis today.